APPLYING AUTHENTIC ASSESSMENT IN CHEMISTRY CURRICULUM STUDIES - Febriana, Beta Wulan; Arlianty, Widinda Normalia (Proceedings of the International Conference on Education, 2017)
One of the growing issues in Indonesia is changing curriculum. Nowadays, most of high school using two different curriculum. Teacher candidates must be understand and differentiate between that two curriculum was applied. The purpose of the study was to investigate the effect of authentic assessment on the teacher candidates in Chemistry Education. This study was used Classroom Action Research using two cycles of learning. The sample were teacher candidates of Chemistry Education 4th semester in academic year 2016/2017. The learning approach used is Contextual Teaching and Learning. Data collection techniques used is testing method and nontesting methods. The test method consists of tests for cognitive, on the other hand, the non-test methods using a Likert scale questionnaire and an observation sheet. The tool of authentic assessment consisted of reviewing aspects of knowledge, attitudes, and self-efficacy and peer assessment. The results showed that student achievement increased from the first to second cycles. In the cognitive aspect, the students’ scores increased from 62.00% to 81.67%; in aspects of the attitude that consists of attitude assessment, self-efficacy, and peer assessment in the first cycle of 77.04%; 75.71%; 72.57%, while in the second cycle of 79.07%; 77.62%; 73.61% respectively.